The impact of electric vehicle charging schemes in power system expansion planning. (15th March 2020) - Manríquez, Francisco; Sauma, Enzo; Aguado, José; de la Torre, Sebastián; Contreras, Javier
Highlights: The impacts of massive electric vehicle penetration in long-term power systems expansion planning are analyzed. We use a detailed power transmission and generation co-optimization expansion planning model. We perform an economic evaluation of the operational benefits provided by smart charging. Electric vehicle charging schemes have complementarity with solar power capacity in Chile. In Chile, the benefits of EV smart charging depend on the level of solar power capacity installed. Abstract: This study analyzes the impacts of the massive electrification of vehicles on the power system expansion planning and operation for the year 2030. For this purpose, a long-term generation and transmission expansion co-optimization model is used, which captures the hourly operational dynamics of the system by means of the use of representative days. This is relevant since smart charging schemes for Electric Vehicles (EVs) are available, and their benefits are intertwined with the hourly available generation (especially solar), the level of demand, and the transmission capacity. Private and public EVs' demand is considered through five main scenarios, which differ in the number of EVs and the charging strategies used (i.e., upon-arrival charging or smart charging). The analysis is illustrated using the Chilean power grid. The numerical results show that a massive penetration of EVs in the Chilean power generation system will heavily encourage solar power capacity investments. Furthermore, smart charging allows for an additional increase in the solar power installed, leading (in the Chilean case) to an extra 2.4% increase in solar power generation and an additional 2.5% decrease in fossil fuel-based generation, which was commonly used to offer flexibility to the system. These effects are diminished if a high-enough level of solar power is not feasible. In addition, some sensitivity analyses are made in order to identify the specific influences of some of the model parameters.